Implikasi Pasal Multitafsir UU ITE Terhadap Unsur Penghinaan dan Pencemaran Nama Baik: Implications of the Multi-interpretation Article of the ITE Law on the Elements of Humiliation and Defamation - Rachmawati, Fairus Augustina; Taduri, Januari Nasya Ayu (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
Since the beginning of the enactment of laws and regulations related to Electronic Transfer Information, there have been various pros and cons to several articles that are considered to have multiple interpretations, one of which is Article 27 paragraph 3 regarding insults and defamation. Where in the process, the provisions of the article refer to the offense of complaint, but there is no clear limit on the elements of insult and defamation, poses several threats of problems in the implications of the article, among others: 1) limitation of freedom of opinion guaranteed by the constitution and rights Human Rights, 2) lack of legal certainty, 3) the potential for overcriminalization, 4) the ineffectiveness of the article due to duplication of the Humiliation clause of the Criminal Code, 5) Arbitrary actions against the determination of the defendants by justice enforcers. In other words, the situation of multiple interpretations in the article causes the non- fulfillment of the legal objectives to create certainty, benefit and justice. The focus in this paper is to reaffirm the benchmarks for the elements of insult and defamation of Article 27 Paragraph 3 of the ITE Law which is still considered confusing and causes legal uncertainty and hampers the law enforcement process in Indonesia if the article is implemented. In addition, this paper will later provide solutions to these problems. The legal research method used is normative legal research through a statutory or statutory approach, and uses secondary legal data sources.